(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In this paper, we present the 3D modelling and structural analysis of a telescopic shock absorber unit that have been considered. A telescopic shock absorber unit from railway wheels was used in this study. The 3D model of a telescopic shock absorber unit consists of a cylinder, Belleville disc, eye ball, flange models that were created with the help of CATIA V5 software, and Finite Element Analysis (FEA) is also carried out to find the Equivalent Von-Misses stresses and deformations to reduce the bouncing, stability, and improve the performance of a shock absorber unit.